Generic review of Polycentropodidae with description of 32 new species and 19 new species records from the Oriental, Australian and Afrotropical Biogeographical Regions - Oláh, János; Johanson, Kjell Arne (Zootaxa, 2010)
The taxonomy of the Polycentropodidae is discussed, and the family is divided into 4 newly defined diagnostic genus clusters based primarily on wing characters and number of spurs on the legs. The diagnostic genus clusters are the Neureclipsis diagnostic genus cluster with Neureclipsis McLachlan and Neucentropus Martynov; the Polycentropus diagnostic genus cluster with Polycentropus Curtis, Plectrocnemia Stephens, Holocentropus McLachlan, and Polyplectropus Ulmer; the Cyrnus diagnostic genus cluster with Nyctiophylax Brauer, Cyrnus Stephens, Cyrnopsis Martynov, Cyrnellus Banks, and Adectophylax Neboiss; and the Cyrnodes diagnostic genus cluster with Cyrnodes Ulmer, Cernotina Ross, and Pahamunaya Schmid. The extinct genus Archaeoneureclipsis Ulmer is synonymised with Neureclipsis McLachlan; the extant genus Tasmanoplegas Neboiss is synonymised with Plectrocnemia Stephens; the extant genus Eodipseudopsis Marlier is synonymised with Polyplectropus Ulmer; and the extinct genus Nyctiophylacodes Ulmer is synonymized with Nyctiophylax Brauer. The following 8 new species are described in Plectrocnemia: P. martynovi (Myanmar), P. ambaita (Myanmar), P. kachin (Myanmar), P. taungyia (Myanmar), P. dalat (Vietnam), P. kamba (Myanmar), P. malaisei (Myanmar), and P. thai (Vietnam). The following 11 new species are described in Polyplectropus: P. daimong (Vietnam), P. dinhdan (Vietnam), P. giandi (Vietnam), P. jalan (Malaysia), P. pairavatika (Malaysia), P. vanuatu (Vanuatu), P. coronivia (Fiji), P. palma (Fiji), P. vanda (Fiji), P. vanua (Fiji), and P. wainimbuk (Fiji). The following 2 new species are described in the subgenus Nyctiophylax (Nyctiophylax): N. (N.) hotay (Vietnam) and N. (N.) catunujah (Myanmar). The following 7 new species are described in the subgenus Nyctiophylax (Paranyctiophylax): N. (P.) anosib (Madagascar), N. (P.) buoc (Vietnam), N. (P.) dhauli (India), N. (P.) kilah (Madagascar), N. (P.) lancelot (Malaysia), N. (P.) mintin (Vietnam and Laos), N. (P.) nepenthes (Malaysia). Cyrnopsis tangaron is described from Indonesia (Borneo). And the following 3 new species in Pahamunaya are described: P. espelandae (Brunei), P. wamana (Malaysia) and P. khoii (Vietnam). In addition, new records for 20 species are given.